Sazonal frequency of bacterial vaginosis and candida sp in pap smears observed in a private laboratory in Fortaleza, Brazil, from 2012 to 2015 - Silva, Angeline Maria Holanda Pascoal da; Medeiros, Juliana Teles; Eleutério, Renata Mírian Nunes; Eleutério Junior, José; Passos, Mauro Romero Leal; Gonçalves, Ana Katherinne Silveira; Giraldo, Paulo César (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: The most frequent gynecological complaints are associated with genital infections, which affect the vaginal microbiota, i.e., vaginitis and vaginosis. Bacterial vaginosis (BV) is characterized by a change of the vaginal microbiota from aerobic bacteria to anaerobic bacteria. Vulvovaginal candidiasis (VVC) is a disorder caused by the abnormal growth of yeast type fungi in the mucosa of the female genital tract. Objective: To identify the frequency of BV and Candida sp in Pap (Papanicolaou) smears in a city of Northeastern Brazil, according to the months of the year for a period of four years. Methods: Study of the frequency of the identification of BV and Candida sp in the oncotic cytology tests carried out in the Professor Eleutério Laboratory database in the city of Fortaleza from 2012 to 2015. Results: The average age of the evaluated cases was 34.7 years, varying from 14 to 54 years of age. In 2012, August was the month with a higher frequency of BV (62.96%), and the month of March had the highest frequency of Candida sp (42.35%). In 2013, BV was more prevalent in September (61.98%) and Candida sp in August (47.26%). In 2014, however, the month of June showed most often BV (60.47%) and September had a higher frequency of Candida sp (43.30%). In 2015, it was April the month in which BV was most detected (60.30%), and in June, Candida sp (41.85%). Conclusion: The frequency of bacterial vaginosis was higher than that of Candida sp during four years. The months with the highest frequency of identified pathogens were June, August and September; however, there were no major changes throughout the year.